(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Although several investigators have reported the relationship between bone mineral density (BMD) and mortality in patients on hemodialysis, it is unclear BMD of which site is most strongly associated with mortality. Methods. We examined the factors related to fractures in patients on hemodialysis in 2009. Based on these data, we investigated the influence of BMD of different sites on mortality in this cohort of 81 patients on hemodialysis. BMD was measured at the distal third of the radius (1/3 Rad), lumbar spine, and total hip. Fifteen patients had prevalent vertebral fractures and seven had prevalent hip fractures. The influences of age, body mass index (BMI), serum creatinine (Cr), serum albumin (Alb), dialysis vintage, and parathyroid hormone (PTH, measured as whole PTH) on mortality were also studied. Results. Fifty-two patients died by August 31, 2018. BMD was significantly higher in the survival group than in the deceased group only for the 1/3 Rad group (P < .001). Although patients with prevalent hip or vertebral fractures showed a higher mortality rate than those without fractures, no significant difference was observed. In the deceased group, age was significantly higher, and BMI and Cr levels were significantly lower than those in the survival group (P < .001, P < .05, and P < .01; respectively). After adjustment for these parameters, BMD of the 1/3 Rad remained a significant prognostic factor. Conclusion. Although this was a study with a limited number of patients, BMD of the 1/3 Rad appears to be associated with mortality in patients on hemodialysis. DOI: 10.52547/ijkd.5952